Exploring Idiomatic Expressions in Demi Lovato's 'Heart Attack': A Student Translation - Matoka, Aminah Qurrata Aini; Napu, Novriyanto; Ali, Sri Widyarti (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the accuracy of students' translations of idiomatic expressions in song lyrics. The Data was collected from 24 students in the 4th semester of the English Department at Gorontalo State University. The song lyrics used for the study were from "Heart Attack" by Demi Lovato. Participants were given 30 minutes to translate the lyrics. The research utilized a qualitative method. Data analysis involved two steps: skimming the translations collected from participants and making notes on the presumed data, followed by identifying and classifying the accuracy of the translations. The study found that the quality of accurate translations was higher than that of inaccurate translations. Specifically, 42% of the translations were accurate, 40% were less accurate, and 18% were inaccurate. This indicates that the overall quality of students' translations of idioms is quite good, likely because some idioms in the song are familiar to them.